MULTI LEVEL MARKETING DALAM KAJIAN FIQH MUAMALAH - Wahyudi, Firman (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
Rampant fraud masquerading as MLM, make this business less sympathetic received from the public. One way to distinguish between MLM and Money game is to see whether a business development company that has been listed by the DSA (APLI) or not. In the system, MLM is a network that works in stages by utilizing the results of the sales turnover of not recruiting members. Bonus received was the work of members who have successfully marketed the product to others. Enterprise as the system has set bonuses and rewards for members who successfully achieve sales target at certain levels and indeed the achievement of these targets is a motivation for other members to work hard to market their products. The basic concept, how the system works and products/services are marketed throughout the engagement does not conflict with the principles of Islam is deemed valid and should be developed for the benefit of mankind.